Patient‐reported pain severity and health‐related quality of life in patients with multiple myeloma in real world clinical practice. Issue 1 (10th June 2021) - Ludwig, Heinz; Bailey, Abigail Lucy; Marongiu, Andrea; Khela, Keerun; Milligan, Gary; Carlson, Katherine Brewer; Rider, Alex; Seesaghur, Anouchka
Abstract: Background: The association between patient self‐reported pain severity and health‐related quality‐of‐life (HRQoL) is poorly understood. Aims: This real‐world study of symptomatic multiple myeloma (MM) patients sought to determine how pain severity from a single question asked during routine clinical consultation was associated with HRQoL. Methods and results: Point‐in‐time data on HRQoL of 330 patients with MM (median age 70 years) receiving anti‐myeloma therapy in Germany and Italy from November 2017 through February 2018 were analyzed. HRQoL was assessed using validated questionnaires (Work Productivity and Activity Impairment [WPAI], European Organization for Research and Treatment of Cancer Quality of Life Questionnaire ‐C30 and ‐MY20). Physical pain severity was assessed during clinical consultation by a single question, asking patients to describe their pain as "no pain, " "mild, " "moderate, " or "severe." Associations between patient‐reported pain severity and HRQoL scores were assessed by analysis of variance or χ 2 tests. Ninety‐six of the 330 patients (29.1%) reported moderate to severe pain. Increase in pain severity, from "no" to "severe" pain, was associated with significantly decreased overall HRQoL (mean score 70.2 to 33.3); significant decreases in levels of physical (82.7 to 35.1), social (81.1 to 44.4), emotional (78.1 to 48.3), and role functioning (79.5 to 38.9); and increased levels of WPAI usual activity impairment (35.4 to 71.4), and fatigue burden (26.0 to 68.9) (all p < .001). Conclusion: Higher pain severity, based on a single self‐report question, was associated with poorer HRQoL in patients with MM, thereby supporting the clinical relevance of directly asking patients to self‐evaluate their pain severity.